#### Answer

{-7, 1}

#### Work Step by Step

1. Factor the equation.
$x^{2}$ + 6x - 7 = 0
(x + 7)(x - 1) = 0
2. Apply the zero factor principle.
a) x + 7 = 0
b) x - 1 = 0
3. Solve each equation.
a) x = -7
b) x = 1
The solutions are {-7, 1}.

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

{-7, 1}

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.